Gerakan Baru Kemanusiaan: Filantropi Islam di Yayasan Al-Hidayah, Kampar, Riau - Pramana, M. Agung; Ariadi, Pitra (LP2M UIN Sunan Kalijaga, 2023)
This article discusses the new Islamic philanthropic movement at Tahfidz Al-Hidayah Foundation, Kampar, Riau. However, the Islamic philanthropy initiated by this foundation is different from Islamic philanthropic activities in general. The administrators sacrifice effort in educating and nurturing their students. The concern shown by the administrators included in Islamic philanthropic activities because of persistence on the basis of humanity is the foundation of the Islamic philanthropic reform movement. This article will answer the main question, what is the context of Islamic philanthropic activities at Tahfidz Al-Hidayah foundation? Meanwhile, the following questions that researcher will explore such as how Islamic philanthropic activities have been from the New Order era to the present? To answer these questions, researcher use ethnographic methods sourced from field research at the Tahfidz Al-Hidayah Foundation. Then, researcher analyzes it with relevant previous literature, as well as additional data, researcher use the netnographic method through the Instagram account @yysn_al_hidayah_kampar. The results of the study show that the Tahfidz Al-Hidayah foundation is an Islamic philanthropic renewal movement that aims to increase piety and pious in concern of humanity. Islamic philanthropy are not only in the form of materials such as Zakat, Infaq, Alms, and Endowments (ZISWAF) which seeks to minimize poverty. However, Islamic philanthropic activities can improve the quality of life. As shown by the Tahfidz Al-Hidayah foundation as a movement based on humanity. [Tulisan ini membahas gerakan baru filantropi Islam di Yayasan Tahfidz Al-Hidayah Kampar, Riau. Filantropi Islam yang digagas oleh yayasan ini berbeda dari kegiatan-kegiatan filantropi Islam pada umumnya. Pengurus mengorbankan usaha dalam mendidik dan membina muridnya. Kepedulian yang diperlihatkan oleh pengurus juga termasuk dalam kegiatan filantropi Islam karena kegigihan atas dasar kemanusiaan menjadi landasan dari gerakan pembaruan filantropi Islam. Artikel ini akan menjawab pertanyaan utama yaitu bagaimana konteks kegiatan filantropi Islam yang ada di Yayasan Tahfidz Al-Hidayah ini? Sedangkan pertanyaan lanjutan yang akan peneliti eksplorasi seperti bagaimana kegiatan filantropi Islam dari era Orde Baru hingga saat ini? Untuk menjawab pertanyaan-pertanyaan tersebut, peneliti menggunakan metode etnografi bersumber dari penelitian lapangan (field research) di Yayasan Tahfidz Al-Hidayah. Kemudian penulis menganalisisnya dengan literatur-literatur sebelumnya yang relevan, sebagai data tambahan, peneliti menggunakan metode netnografi melalui akun instagram @yysn_al_hidayah_kampar. Hasil penelitian menunjukkan bahwa Yayasan Tahfidz Al-Hidayah sebagai gerakan pembaruan filantropi Islam yang bertujuan untuk meningkatkan ketakwaan dan kesalehan dalam bentuk kepedulian atas dasar kemanusiaan. Filantropi Islam juga tidak hanya berbentuk materi seperti Zakat, Infaq, Sedekah, dan Wakaf (ZISWAF) yang berupaya meminimalisir kemiskinan. Namun, kegiatan filantropi Islam itu juga bisa dalam bentuk jasa untuk meningkatkan kualitas hidup seseorang. Seperti yang diperlihatkan oleh Yayasan Tahfidz Al-Hidayah sebagai gerakan atas dasar kemanusiaan.]